Werner Syndrome Helicase Is Required for the Survival of Cancer Cells with Microsatellite Instability - Kategaya, Lorn; Perumal, Senthil K.; Hager, Jeffrey H.; Belmont, Lisa D. (iScience, 2019)
Werner syndrome protein (WRN) is a RecQ enzyme involved in the maintenance of genome integrity. Germline loss-of-function mutations in WRN led to premature aging and predisposition to cancer. We evaluated synthetic lethal (SL) interactions between WRN and another human RecQ helicase, BLM, with DNA damage response genes in cancer cell lines. We found that WRN was SL with a DNA mismatch repair protein MutL homolog 1, loss of which is associated with high microsatellite instability (MSI-H). MSI-H cells exhibited increased double-stranded DNA breaks, altered cell cycles, and decreased viability in response to WRN knockdown, in contrast to microsatellite stable (MSS) lines, which tolerated depletion of WRN. Although WRN is the only human RecQ enzyme with a distinct exonuclease domain, only loss of helicase activity drives the MSI SL interaction. This SL interaction in MSI cancer cells positions WRN as a relevant therapeutic target in patients with MSI-H tumors. [Display omitted] •Decreasing WRN expression negatively affects the survival of MSI-H cells•An increase in DSBs and altered cell cycles preceded MSI-H viability loss•WRN helicase inhibitors may be a beneficial therapy for patients with MSI-H cancers Biological Sciences; Cancer; Molecular Biology